Fruit and vegetable flavour : recent advances and future prospects - Brückner, Bernhard; Wyllie, S. Grant (Woodhead Publishing in food science and technology., 2008)
Consumer acceptance of food is highly dependent on flavour. This important collection reviews the chemical basis of fruit and vegetable flavour and current methods for improving the flavour of fruit and vegetable products. Opening chapters outline the economic importance of flavour in fruit and vegetables. Part one investigates the formation of fruit and vegetable flavour and how it deteriorates after harvest. Part three contains chapters on flavour management during horticultural and postharvest operations. Chapters discuss the possibilities and limitations for flavour improvement by selection and breeding, and the role of maturity for improved fruit and vegetable flavour. Part four concludes the volume with a discussion of emerging trends in flavour manipulation, especially how knowledge of the genetic background of quality attributes can be applied to flavour improvement. With its team of experienced international contributors Fruit and vegetable flavour: recent advances and future prospects is an essential reference for all those working in the food industry concerned with improving flavour in fruit and vegetables. Reviews the chemical basis of fruit and vegetable flavour and current methods for improvementDiscusses the possibilities and limitations for flavour enhancement by selection and breedingIllustrates how knowledge of the genetic background of quality attributes can be applied to flavour improvement.